Casa Cuadrau : yoga, art, and nature in the Spanish Pyrenees - Reddy, Roopa; Rose, David, active 2019 (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Casa Cuadrau is a yoga retreat center in the Spanish Pyrenees. It is the result of a dream that both of its founders, Dani and Katya, had for many years. In December 2013, after the first full season of operation, Dani and Katya are considering where they should focus their marketing efforts for the next year. They are worn out, but can't afford to hire additional staff without increasing revenues. They feel that there are many possible marketing alternatives, but are not sure which is the best direction to take.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Po, Daniel Benito; Chv`ez, Katya Ro?s.; Casa Cuadrau; Yoga -- Marketing -- Case studies; Entrepreneurship -- Pyrenees -- Case studies; Entrepreneurship -- Spain -- Case studies